EFFICIENCY AND STABILITY OF ISLAMIC BANKING IN ASEAN: DEA WINDOW ANALYSIS - Nailah Nailah; Aam Slamet Rusydiana (Tazkia Islamic Finance and Business Review, 2020)
The study aims to analyze stability and efficiency of the Islamic banking industry in the Association of Southeast Asian Nations (ASEAN) region. Islamic banks are currently in the spotlight for their role in Islamic financial growth across South East Asia, especially in Indonesia. The efficiency and stability of Islamic banking is one factor in measuring the readiness of Islamic banks within the ASEAN Economic Community (AEC) framework. This research examines 12 Islamic banks in Indonesia, Malaysia, Brunei Darussalam and Thailand during the 2013-2018 period. The analysis was conducted with a non-parametric approach, namely DEA Window Analysis (DEWA). The results show that Malaysia has the highest average efficiency in four different periods with 96% and Indonesia has an average efficiency of 67%. Thailand with an average efficiency that is relatively stable at 100% and Brunei Darussalam's average efficiency is 55%, lower compared to other countries. For Islamic banks with good stability conditions are Bank Islam Malaysia Berhad and Islamic Bank of Thailand. Meanwhile, Islamic banks with unstable condition are Bank Mega Syariah and Bank Islam Brunei Darussalam. Overall, Islamic banks in ASEAN have achieved stable performance, even though most of them are still inefficient.